Percepções de alunos e professores da rede pública municipal de ensino fundamental de Uruguaiana acerca da educação sexual na escola - Moreira, Betina Loitzenbauer da Rocha (2011)
The theme of sexuality requires courage and a good degree of technical knowledge to address this sensitive topic in the classroom. The theme of sexual orientation is part of the National Curriculum and cross-content and must be worked through all the disciplines, explaining the relationships between the various areas of knowledge. The aim of this study was to understand the perceptions of students and teachers from the municipal public elementary school in Uruguaiana about sex education in school to subsidize the construction and evaluation of a primer on sexuality. The collected data were analyzed using content analysis of Bardin. From the analysis of the results, we found that most of the questions and curiosities of students were related to anatomical and physiological changes, the affection, sexual initiation, sexual identity and sexual orientation, contraception, abortion, teenage pregnancy, types, symptoms and prevention of sexually transmitted diseases and the characterization of sexual violence. We found that sex education was the theme worked in school, depending on the student's needs and interests of the teacher, with students between 6th and 8th grades. Teachers received training to develop the theme in the classroom, with the ease students' interest as the main difficulties and the lack of training, the resistance of colleagues, teachers and lack of family participation in the discussion of this issue. We found that the booklet prepared and evaluated can collaborate in developing this theme, by answering questions, assisting in the introduction and/or development of various topics related to sexuality in school and at home. We note the importance of research regarding the perceptions of adult reference and practice developed in the school, as well as the need for continuing education programs on sexual education in schools for educational and health in partnership between the Department of Education and Secretary of health. We conclude that the work of sex education in school is necessary and important to promote a healthy and responsible interaction between/among teens.